2012
DOI: 10.1016/j.aim.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity of eigenvalues of generalized Wigner matrices

Abstract: Consider N × N hermitian or symmetric random matrices H with independent entries, where the distribution of the (i, j) matrix element is given by the probability measure νij with zero expectation and with variance σ 2 ij . We assume that the variances satisfy the normalization condition i σ 2 ij = 1 for all j and that there is a positive constant c such that c ≤ N σ 2 ij ≤ c −1 . We further assume that the probability distributions νij have a uniform subexponential decay. We prove that the Stieltjes transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
607
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 314 publications
(638 citation statements)
references
References 51 publications
(178 reference statements)
18
607
0
13
Order By: Relevance
“…Local laws have become a cornerstone in the analysis of spectral properties of large random matrices [4,8,20,23,29,35,37,51]. In its simplest form, a local law considers the normalized trace 1 N Tr G(ζ ) of the resolvent.…”
Section: A := E H S[r] := E (H − A)r(h − A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Local laws have become a cornerstone in the analysis of spectral properties of large random matrices [4,8,20,23,29,35,37,51]. In its simplest form, a local law considers the normalized trace 1 N Tr G(ζ ) of the resolvent.…”
Section: A := E H S[r] := E (H − A)r(h − A)mentioning
confidence: 99%
“…Local laws are the first step of a general three step strategy developed in [24,25,27,29] for proving universality. The second step is to add a tiny independent Gaussian component and prove universality for this slightly deformed model via analyzing the fast convergence of the Dyson Brownian motion (DBM) to local equilibrium.…”
Section: ) Then S[g] Is Still Random and We Have S[g] = E ( H − A)g(mentioning
confidence: 99%
“…Below this scale the eigenvalue density remains fluctuating even for large N . In [25] the Green function G(z) and its average m(z) have been used to prove edge universality for generalized Wigner matrices. In [32] we derived a local deformed semicircle law for the deformed ensemble (1.1) under the assumption that µ f c has a square root behavior at the endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of papers [20,21,22] Erdős, Schlein and Yau showed that the semicircle law for Wigner matrices also holds down to the optimal scale 1/N , up to logarithmic corrections. In [24] a "fluctuation average lemma" was introduced that yielded optimal bounds on the convergence of m(z) for Wigner matrices in the bulk [24] and up to the edge [25] on scales η ≫ N −1 . Below this scale the eigenvalue density remains fluctuating even for large N .…”
Section: Introductionmentioning
confidence: 99%
“…≤ γ nn , the quantiles of G, i.e. G(γ nj ) = j n , and introduce the notation llog n := log log n. Erdös et al [6], [7] showed, for matrices with elements X jk which have a uniformly sub exponential decay, i.e.…”
Section: Introductionmentioning
confidence: 99%